ANALISIS PENGARUH SUHU PENYIMPANAN TERHADAP KARAKTERISTIK FISIK JAJANAN TRADISIONAL GETTAS - A Zainul Faruq; Ahmad Mundzir Romdhani; Moh. Nurul Hidayatullah (TAPE : Jurnal Teknologi Hasil Pertanian, 2024)
Gettas a traditional snack, is one of the homemade traditional treats. The producers of gettas, who are the target audience of this endeavor, are guided by their family heritage. The primary ingredient used in making gettas is glutinous rice flour. Other ingredients include coconut milk, granulated sugar,salt, and cooking oil. One of the challenges faced with this traditional snack is determining the appropriate storage temperature. Improper storage can affect the physical characteristics of gettas. The objective of this research is to identify the optimal storage temperature to maintain the physical attributes of gettas. The research methodology employed physical tests, encompassing parameters such as aroma, color, and texture. The findings of the research reveal that storage temperature does not significantly influence the physical attributes of gettas. However, the most suitable storage temperature to preserve the physical characteristics of gettas is refrigerator temperature, or 4°C.